2013
DOI: 10.1021/jf400541q
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Functional Nanothin Multilayers on Food Packaging: Ice-Nucleating Polyethylene Films

Abstract: Polyethylene is the most prevalent plastic and is commonly used as a packaging material. Despite its common use, there are not many studies on imparting functionalities to those films which can make them more desirable for frozen food packaging. Here, commercial low-density polyethylene (LDPE) films were oxidized by UV-ozone (UVO) treatment to obtain a negatively charged hydrophilic surface to allow fabrication of functional multilayers. An increase in hydrophilicity was observed when films were exposed to UVO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Our previous work demonstrated that building more bilayers had an effect on both on the surface morphology and the absorption of ECINs as top layer on the PDDA/PSS system (Gezgin et al, 2013). Here the observations were similar with the AFM images showing more concentrated carrageenan gel networks with thicker and more elevated threads on the surface of higher contrast as the number of bilayers increase ( Figure 2).…”
Section: Effect Of the Number Of Bilayers Formed On Surface Morphologsupporting
confidence: 84%
See 1 more Smart Citation
“…Our previous work demonstrated that building more bilayers had an effect on both on the surface morphology and the absorption of ECINs as top layer on the PDDA/PSS system (Gezgin et al, 2013). Here the observations were similar with the AFM images showing more concentrated carrageenan gel networks with thicker and more elevated threads on the surface of higher contrast as the number of bilayers increase ( Figure 2).…”
Section: Effect Of the Number Of Bilayers Formed On Surface Morphologsupporting
confidence: 84%
“…They are used in food systems to increase freeze-thaw resistance, modify food texture and deliver energy savings in freeze drying and concentration applications (Li-Jung, Chen, Tzeng, Chiou & Jiang, 2005;Zhu & Lee, 2007) There are no reports regarding the activity of ice nucleators when applied as a nano-thin layers in food products. ECIN nano-thin films have been fabricated using non-food grade synthetic oppositely charged cationic poly (diallyldimethylammonium chloride) and anionic poly (styrenesulfonate) (Gezgin, Lee & Huang, 2013). Thus it is of importance to consider the fabrication of ECIN nano-thin films using food grade polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In two dimensions (2D), two dimensions are in nanoscale, and one dimension is in macroscale. Coating solid surfaces with nanomaterials creates 2D-like structures (e.g., nano-sheets, nano-walls, nano-thin-films, or nano-thin-multilayers) [ 61 ]. Keeping the thickness constant in the nanoscale range, the total area of nanomaterials’ 2D-like structures could be within some square micrometers.…”
Section: Impact Of Nanomaterials On Biosensor Performancementioning
confidence: 99%
“…We have demonstrated earlier that ECIN nano‐thin films can be fabricated on a surface through electrostatic interactions using nonfood grade synthetic oppositely charged cationic poly (diallyldimethylammonium chloride) (PDDA) and anionic poly(styrenesulfonate) (PSS; Gezgin, Lee, & Huang, 2013). A similar work on ice propagation had been conducted using the layer by layer (LbL) deposition of polyelectrolyte pairs PSS/poly(allylamine hydrochloride) (PAH) and PSS/PDDA without using ECINs, where authors concluded that ice propagation can be tuned by modifying the outermost polymer layer (Jin, He, Guo, & Wang, 2017), which in fact was performed in our above cited work by adding a single layer of ECINs on the PSS/PDDA multilayers.…”
Section: Introductionmentioning
confidence: 99%